Dermoscopic Characteristics of Melanoma According to the Criteria "Ulceration" and "Mitotic Rate" of the AJCC 2009 Staging System for Melanoma - Deinlein, T (2017)
OBJECTIVE: The present study was conducted to identify possible dermoscopic patterns, associated with mitotic rate > 1/mm2, histological ulceration in melanoma and metastatic disease. METHODS: For this retrospective data analysis all clinical and dermoscopic digital images of primary malignant melanomas between 2008 and 2013 documented at the Department of Dermatology Graz were included, using the internal image data-base. 550 patients with 559 melanomas were included. RESULTS: While clinical or dermoscopic analysis considered ulceration to be present in 120 (21.5%) and 117 (20.9%) of all lesions, respectively, histopathology reported ulceration in only 96 cases (17.2%). The presence of milky-red areas, shiny-white streaks, a blue-white veil and blue-grey areas in dermoscopy is highly correlated with histological ulceration and a mitotic rate > 1/mm2. The dermoscopic patterns shiny-white streaks, milky-red areas and blue-white veil were also significantly associated with development of distant metastases. CONCLUSION: Our study proves a significant correlation between the dermoscopic patterns "blue white veil", "milky-red areas"and "shiny-white streaks"and the histological findings "ulceration"and "mitotic rate > 1/mm2". Furthermore these dermoscopic patterns are highly related to distant metastases. Thus, dermoscopy renders earlier prognostic statements possible.